Implementation and dissemination of an African American popular opinion model to improve lupus awareness: an academic–community partnership. (October 2019) - Phillip, C R; Mancera-Cuevas, K; Leatherwood, C; Chmiel, J S; Erickson, D L; Freeman, E; Granville, G; Dollear, M; Walker, K; McNeil, R; Correia, C; Canessa, P; et al.
Objective: Lupus is a chronic, autoimmune disease that disproportionately affects African Americans. We adapted the Centers for Disease Control and Prevention's Popular Opinion Leader model to implement an intervention tailored for African American individuals that leverages an academic-community partnership and community-based social networks to disseminate culturally appropriate lupus education. Methods: Academic rheumatologists, social scientists, and researchers in Boston, MA and Chicago, IL partnered with local lupus support groups, community organizations, and churches in neighborhoods with higher proportions of African Americans to develop curriculum and recruit community leaders with and without lupus (Popular Opinion Leaders; POLs). POLs attended four training sessions focused on lupus education, strategies to educate others, and a review of research methods. POLs disseminated information through their social networks and recorded their impact, which was mapped using a geographic information system framework. Results: We trained 18 POLs in greater Boston and 19 in greater Chicago: 97% were African American, 97% were female; and the mean age was 57 years. Fifty-nine percent of Boston POLs and 68% of Chicago POLs had lupus. POLs at both sites engaged members of their social networks and communities in conversations about lupus, health disparities, and the importance of care. Boston POLs documented 97 encounters with 547 community members reached. Chicago POLs documented 124 encounters with 4083 community members reached. Conclusions: An adapted, community-based POL model can be used to disseminate lupus education and increase awareness in African American communities. Further research is needed to determine the degree to which this may begin to reduce disparities in access to care and outcomes.